Walking with blood flow restriction on lower limb muscles post-ACL reconstruction: A within-subject trial - Letícia Pophal Cutisque; John Gerard Buckley; André Luiz Felix Rodacki (PLoS ONE, 2025)
Background Individuals recovering from anterior cruciate ligament (ACL) reconstruction often exhibit persistent strength deficits that can impair function and delay return to participation in sport and/or physical activity. Blood flow restriction (BFR) training has emerged as a promising strategy to enhance muscle adaptations using low-load exercises, but its effectiveness when combined with walking training in this population remains unclear. Objective To determine the effectiveness of a walking program combined with BFR on muscle strength and thickness at the ankle and knee in patients with ACL reconstruction. Methods This within-subject clinical trial included 40 adults (27.1 ± 7.3 years; 21 females, 19 males) who had undergone ACL reconstruction at least 6 months prior and presented with a ≥ 10% strength deficit in the knee extensor muscles of the operated limb. Participants completed a 12-week progressive walking program, with duration (from 12 to 20 minutes) and speed (from 1.25 to 2.00 m.s-1) being progressively increased over the 12 weeks. BFR at 90% occlusion pressure was applied to the weaker limb (WL), while the contralateral limb served as control (CL). The intervention included one supervised and two home-based walking sessions per week. Post-intervention outcomes involved determining changes from baseline in peak torque (PT) of ankle and knee extensors and flexors, as well as muscle thickness (MT) of the gastrocnemius medialis (GM), tibialis anterior (TA), vastus lateralis (VL), and semitendinosus (ST). Results Ankle plantarflexor PT increased in both limbs (WL = 51.6%; CL = 11.7%), while dorsiflexor PT increased slightly in the WL (5%). GM thickness increased in both limbs (WL = 1.1%; CL = 0.5%), with no changes in TA. For the knee extensors and flexors, PT increased in both limbs (WL = 33.1% and 25.7%; CL = 14.9% and 8.9%). No significant MT changes were observed in VL or ST. Conclusions A progressive walking program with BFR was associated with increases in lower limb strength and modest MT changes in individuals post-ACL reconstruction. These findings suggest that this intervention may represent a safe and potentially efficient adjunct to post-ACL rehabilitation. Trial registration: RBR-5gqgs99. https://ensaiosclinicos.gov.br/rg/RBR-5gqgs99.